Mobile-assisted Language Learning In Efl Classes: Stance And Hampers Of Embodiment - Yala, Ahmed; Keskes, Said (جامعة الوادي - University of Eloued, 2020)
To reconnoiter the position of Mobile-Assisted Language Learning (MALL) in EFL classes and discover the challenges of its implementation, 24 students and 21 teachers from the department of English language and literature at Sétif 2 University have been sampled. The data derived after qualifying the interview discussions with students and quantifying the questionnaire responses of teachers. The outcomes entailed a scarce presence of mobile based instruction in comparison to the other Information and Communication Technologies (ICTs). As to scrutinize the factors, issues of affordance, teachers’ lack of training and students’ knowledge have been reported as impacting the embodiment of mobile learning in EFL classes. To overcome allied hindrances and concretize awareness of the concept, insightful implications and pedagogical actions have been drawn for practice.
مقال
Keywords: MALL, ICTs, EFL teachers, EFL students, Challenges of embodiment